Effects of bismuth subsalicylate and encapsulated calcium ammonium nitrate on ruminal fermentation of beef cattle. (8th July 2020) - Henry, Darren D; Ciriaco, Francine M; Araujo, Rafael C; Fontes, Pedro L P; Oosthuizen, Nicola; Mejia-Turcios, Sebastian E; Garcia-Ascolani, Mariana E; Rostoll-Cangiano, Lautaro; Schulmeister, Tessa M; Dubeux, Jose C B; Lamb, G Cliff; DiLorenzo, Nicolas
Abstract: A replicated 5 × 5 Latin square design with a 2 × 2 + 1 factorial arrangement of treatments was used to determine the effects of bismuth subsalicylate (BSS ) and encapsulated calcium ammonium nitrate (eCAN ) on ruminal fermentation of beef cattle consuming bahiagrass hay ( Paspalum notatum ) and sugarcane molasses. Ten ruminally cannulated steers ( n = 8; 461 ± 148 kg of body weight [BW ]; average BW ± SD) and heifers ( n = 2; 337 ± 74 kg of BW) were randomly assigned to one of five treatments as follows: 1) 2.7 g/kg of BW of molasses (NCTRL ), 2) NCTRL + 182 mg/kg of BW of urea (U ), 3) U + 58.4 mg/kg of BW of BSS (UB ), 4) NCTRL + 538 mg/kg of BW of eCAN (NIT ), and 5) NIT + 58.4 mg/kg of BW of BSS (NITB ). With the exception of NCTRL, all treatments were isonitrogenous. Beginning on day 14 of each period, ruminal fluid was collected and rectal temperature was recorded 4× per day for 3 d to determine ruminal changes every 2 h from 0 to 22 h post-feeding. Ruminal gas cap samples were collected at 0, 3, 6, 9, and 12 h on day 0 of each period followed by 0 h on days 1, 2, 3, and 14. Microbial N flow was determined using Cr-Ethylenediaminetetraacetic acid, YbCl3, and indigestible neutral detergent fiber for liquid, small particle, and large particle phases, respectively. Data were analyzed using the MIXED procedure of SAS. Orthogonal contrasts were used to evaluate the effects of nonprotein nitrogen (NPN ) inclusion, NPN source, BSS, and NPN source × BSS. There was no treatment effect ( P > 0.05) on concentrations of H2 S on day 0, 1, 2, or 14; however, on day 3, concentrations of H2 S were reduced ( P = 0.018) when NPN was provided. No effect of treatment ( P = 0.864) occurred for ruminal pH. There was an effect of NPN source on total concentrations of VFA ( P = 0.011), where a 6% reduction occurred when eCAN was provided. There were effects of NPN ( P = 0.001) and NPN source ( P = 0.009) on the concentration of NH3 -N, where cattle consuming NPN had a greater concentration than those not consuming NPN, and eCAN reduced the concentration compared with urea. Total concentrations of VFA and NH3 -N were not affected ( P > 0.05) by BSS. There was an effect of BSS ( P = 0.009) on rectal temperature, where cattle not consuming BSS had greater temperatures than those receiving BSS. No differences for NPN, NPN source, nor BSS ( P > 0.05) were observed for microbial N flow. In conclusion, eCAN does not appear to deliver equivalent ruminal fermentation parameters compared with urea, and BSS has limited effects on fermentation.